2014
DOI: 10.1177/0886260514540324
|View full text |Cite
|
Sign up to set email alerts
|

The Co-Occurrence of Physical and Cyber Dating Violence and Bullying Among Teens

Abstract: This study examined the overlap in teen dating violence and bullying perpetration and victimization, with regard to acts of physical violence, psychological abuse, and-for the first time ever-digitally perpetrated cyber abuse. A total of 5,647 youth (51% female, 74% White) from 10 schools participated in a cross-sectional anonymous survey. Results indicated substantial co-occurrence of all types of teen dating violence and bullying. Youth who perpetrated and/or experienced physical, psychological, and cyber bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
4
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 6 publications
6
59
4
9
Order By: Relevance
“…Cyberbullying and cyberhate perpetration were positively associated (H1). This is both consistent with problem behaviour theory (Jessor & Jessor, 1977), and with previous research, which found that when young people are involved in one form of cyberaggression as perpetrators, then they are more likely to also be involved in others (Olweus, 2012;Wachs et al, 2015;Yahner et al, 2015;Zezulka & Seigfried-Spellar, 2016). This finding can be explained by common set of risk factors or antecedents, as theoretically hypothesised by the theory, including low self-control, anger regulation, or lower levels of empathy, all of which need to be further investigated in future research.…”
Section: Discussionsupporting
confidence: 92%
“…Cyberbullying and cyberhate perpetration were positively associated (H1). This is both consistent with problem behaviour theory (Jessor & Jessor, 1977), and with previous research, which found that when young people are involved in one form of cyberaggression as perpetrators, then they are more likely to also be involved in others (Olweus, 2012;Wachs et al, 2015;Yahner et al, 2015;Zezulka & Seigfried-Spellar, 2016). This finding can be explained by common set of risk factors or antecedents, as theoretically hypothesised by the theory, including low self-control, anger regulation, or lower levels of empathy, all of which need to be further investigated in future research.…”
Section: Discussionsupporting
confidence: 92%
“…Frequent co-occurrence of cyberbullying and online dating abuse has been described in younger adolescents. 47 In the college population, electronic relationship violence has also been described and associated with alcohol use. 48,49 Cyberstalking is a manifestation of such abuse among college students, and in adult samples is associated with decreased well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in cyber DV victimization have been previously analyzed, but without conclusive results [14]. Some studies have shown more cyber DV victimization in girls [7,8,45], while others have indicated more cyber victimization in boys [3,46]. In studies differentiating between cyber-control and cyber-aggression, more involvement of boys in cyber-aggression behaviors and a similar involvement of boys and girls in cyber-control behaviors have been observed [22].…”
Section: Offline and Cyber Dating Violence Victimizationmentioning
confidence: 99%